9 Stat. at Large of S.C. 633 (1841) - (:unkn) unknown (My University, 1721)
"Acts relating to the Militia," Stateutes at Large of South Carolina No. 440: Required that master or mistress provide "every white male servant or servants… at the term and exdpirtation of his or their srvice be freed and discharged shall be provided with such good and sufficient arms, ammunition, and accoutrments, as by this act is directed..."
Keywords: GUARANTEED RIGHT